Addition Of Tadarus of The Qur'an in Improving Students' Religious Character at Madrasah Ibtidaiyah Negeri 1 Boyolali Academic Year 2023/2024 - Sulismiyati; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
This research aims to find out how the practice of reciting Al-Qur'an in improving religious character at Madrasah Ibtidaiyah Negeri 1 Boyolali. This research is a qualitative descriptive study. The subject of this research was the MIN 1 Boyolali class teacher. This research was conducted at MIN 1 Boyolali from October to December with research informants, namely, the school principal, PAI teachers, class teachers and students. Data was obtained through observation, interviews and documentation as well as the results of relevant literature. Meanwhile, data analysis is divided into several stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that at MIN 1 Boyolali the habit of tadarus is carried out every day before class starts and after the Duha prayer activities. The supporting factors are adequate learning facilities and teacher motivation. Meanwhile, the inhibiting factors for the tadarus habituation activities at MIN 1 Boyolali are that the ability to read the Al-Qur'an for some students is still not fluent, there are teachers who do not master there citation of the Al-Qur'an because their educational background is general, and the discipline of teachers and students is still lacking.